HISTOLOGICAL EVALUATION OF INDIRECT PULP CAPPING PROCEDURES WITH CALCIUM HYDROXIDE AND MINERAL TRIOXIDE AGGREGATE - Monea, Monica; Monea, Adriana; Stoica, Alexandra (European Scientific Journal, ESJ, 2014)
Objective: to obtain a histological comparison of tertiary dentin after indirect pulp capping procedures using calcium hydroxide or MTA in teeth with deep carious lesions, regarding its morphological characteristics and degree of inflammation induced in the dental pulp. We used 60 third molars with occlusal caries lesions from 30 patients of 17-26 years of age. Class I and II deep cavities were prepared and randomly restored with calcium hydroxide or MTA and glass ionomer cement. The histologic specimens were obtained at 2-4-6 weeks and the evaluation was done by the same person in a double blind manner.The results showed statistical significant differences between these capping materials regarding the formation rate and morphology of tertiary dentin induced by indirect pulp capping procedures. Conclusion: the success of this therapy is conditioned by the use of dental materials that contain or can deliver calcium hydroxide, completed with a final restoration without marginal leakage, which prevents microbial infiltration from oral cavity.